Konsep negara hukum (rule of law) pancasila dalam sistem ketatanegaraan indonesia - tunisa, Dinda safira (Maliki Interdisciplinary Journal, 2026)
Since Indonesia’s independence, the idea that government must operate on the basis of the rule of law has been explicitly articulated in the Elucidation of the 1945 Constitution; however, in practice, the implementation of this principle has not been fully realized, particularly during the period following the Presidential Decree of 5 July 1959 and throughout the New Order era, when—despite claims of implementing Pancasila and the 1945 Constitution in a pure and consistent manner—the law was frequently used as an instrument of development, thereby opening space for authoritarian governance. In the Reform era, the commitment to a law-based state was reinforced through Article 1 paragraph (3) of the amended 1945 Constitution, which explicitly affirms Indonesia as a state governed by law, although its application continues to face significant challenges such as sectoral interests, group-based motivations, and conflicting political dynamics. Historically, the concept of rechtsstaat, introduced to Indonesia since the enactment of the Regeringsreglement (RR) of 1854 and later reflected in the drafting of the 1945 Constitution, emphasizes the protection of individual freedoms and equality before the law, while the concept of the rule of law highlights the supremacy of law and the realization of substantive justice that must not be confined to formal legal application or reduced to mere rule by law.